Correlation Between Bile Reflux Gastritis and Biliary Excreted Contrast Media in the Stomach. Issue 5 (September 2017) - Hyun, Jong Jin; Yeom, Suk Keu; Shim, Euddeum; Cha, Jaehyung; Choi, Inyoung; Lee, Seung Hwa; Chung, Hwan Hoon; Cha, Sang Hoon; Lee, Chang Hee
Abstract : Objective: This study aimed to evaluate the relationship between biliary excreted contrast media in the stomach and the presence of bile reflux gastritis. Methods: Consecutive 111 patients who underwent both gadoxetic acid–enhanced magnetic resonance cholangiography (gadoxetic MRC) and gastric endoscopy were included in this study. We performed a review of the gadoxetic-MRC image sets acquired 60 minutes after intravenous injection of contrast media and endoscopic images. We recorded amount of contrast media in the stomach. The sensitivity, specificity, and accuracy of duodenogastric bile reflux diagnosis were evaluated for the gadoxetic MRC. Statistical analysis was performed using the Fisher exact test and the linear-by-linear association test. Results: Among the 111 patients, 39 had 60-minute delayed images showing the presence of contrast media in the stomach. Of these 39 patients, 13 had bile reflux gastritis and 5 showed bile in the stomach without evidence of erythematous gastritis. Of the 72 patients who did not show contrast media in the stomach, none had bile reflux gastritis and 2 patients showed bile staining in the stomach without evidence of erythematous gastritis. Bile reflux gastritis was significantly more frequent in patients with contrast media in the stomach on gadoxetic MRC than in those without. Patients with high-grade extension of contrast media in the stomach had significantly frequent bile reflux gastritis than did those with low-grade extension. Conclusion: Biliary excreted contrast media in the stomach on 60-minute delayed gadoxetic MRC has a correlation with the presence of bile reflux gastritis on endoscopic examination.